Boosting third-harmonic generation by a mirror-enhanced anapole resonator - Xu, Lei; Rahmani, Mohsen; Zangeneh Kamali, Khosro; Lamprianidis, Aristeidis; Ghirardini, Lavinia; Sautter, Jürgen; Camacho-Morales, Rocio; Chen, Haitao; Parry, Matthew; Staude, Isabelle; Zhang, Guoquan; Neshev, Dragomir; et al. (Light, science & applications, 2018)
We demonstrate that a dielectric anapole resonator on a metallic mirror can enhance the third harmonic emission by two orders of magnitude compared to a typical anapole resonator on an insulator substrate. By employing a gold mirror under a silicon nanodisk, we introduce a novel characteristic of the anapole mode through the spatial overlap of resonantly excited Cartesian electric and toroidal dipole modes. This is a remarkable improvement on the early demonstrations of the anapole mode in which the electric and toroidal modes interfere off-resonantly. Therefore, our system produces a significant near-field enhancement, facilitating the nonlinear process. Moreover, the mirror surface boosts the nonlinear emission via the free-charge oscillations within the interface, equivalent to producing a mirror image of the nonlinear source and the pump beneath the interface. We found that these improvements result in an extremely high experimentally obtained efficiency of 0.01%. Dielectric nanophotonics: mirror-enhancement The use of a thin metallic substrate can dramatically enhance the magnitude of third harmonic generation (THG) that is possible from a silicon nanodisk anapole resonator. Lei Xu and coworkers from Australia, Italy, Germany and China fabricated 200nm-thick amorphous silicon nanodisks on a gold film. As with other dielectric nanostructures, the silicon nanodisk supports nonradiating anapole states that result from the destructive interference of electric and toroidal dipole moments in the far-field. At the same time, such anapole states provide near-field enhancement inside the silicon nanodisk and can strengthen nonlinear effects such as THG. Xu and coworkers have now found that the THG can be further boosted by another two orders of magnitude to reach a conversion efficiency of 0.01% by using a gold film substrate to generate a virtual mirror image that coherently amplifies the structure’s nonlinear response.